Study on some risk factors affecting low birth weights born at Base Hospital Gampaha. - Pallewatte, N.C (My University, 1998)
A case control study was carried out in the base hospital,Gampaha,during the period of 1st of April 1997 to 30 th of August 1997.Babies bron to sinhala buddhist primipara mothers with uncomplicated obstetric history during such period were selected for the study.Babies who weighed below 2,500 grams at birth were considered as "cases" and those who weighed 2,500 grams or over were considered as "controls".The following recommendations were made in accordance with results of the study.To increase awareness among the general public about the best age for first child birth and improvement of family planning services.To make mesures to reduce occupational hazards during pregnancy with the collaboration of employers.To take appropriate steps to increase nutritional status of the pregnant women and adolescent girls.To provide facilities for early detection of anaemia and regular weighing of pregnant mothers at ante natal clinics.To inculcate health education more meaningfully stressing the need to follow all accepted health practices.